Bovine attaching and effacing Escherichia coli possess a pathogenesis island related to the LEE of the human enteropathogenic Escherichia coli strain E2348/6950 - Goffaux,F.; J.G. Mainil; Pirson,V.; Charlier,G.; Pohl,P.; Jacquemin,E.; Bernard China (FEMS Microbiol.Lett., 1997)
Attaching and effacing Escherichia coli (AEEC) has been described as a cause of diarrhea in calves. The molecular pathogenesis of AEEC was mainly studied in human enteropathogenic E. coli strain E2348/69 in which the virulence correlated with the presence of a 35.4 kb pathogenesis island called LEE. We showed that several strains isolated from calves with diarrhea were able to produce attaching and effacing lesions in a rabbit ileal loop model and that they possess a pathogenesis island related to the LEE. Moreover, we showed that the LEE from bovine strains was inserted mainly at a different position in the chromosome compared to the human enteropathogenic E. coli strain E2348/69
Keywords: a; Animals; article; AS; at; Belgium; Cattle; Cattle Diseases; cause; Chromosome Mapping; Diarrhea; e; Escherichia coli; Faculty; Human; Humans; im; IS; journal; Laboratories; Medicine; microbiology; MODEL; Molecular; pathogenicity; polymerase chain reaction; Print; rabbit; Rabbits; Research; Research Support; SB - IM; strain; Universities; university; veterinary; Veterinary Medicine; virulence